The Lanternfly genus Pyrops in Vietnam: A new species from Central Vietnam, taxonomic changes, checklist, identification key (Hemiptera: Fulgoromorpha: Fulgoridae) - Constant, Jérôme; Pham, Hong Thai (European Journal of Taxonomy, 2022)
A new species of the genus Pyrops Spinola, 1839 (Fulgoridae), P. buomvoi sp. nov., is described from Ca Na, Ninh Thuan Province in Central Vietnam. It is attributed to the candelaria group and compared with the other species of the genus. Pyrops lathburii (Kirby, 1818) is proposed as a senior synonym of P. astarte (Distant, 1914), transferred back to the candelaria group from the pyrrhorhynchus group, and recorded from Laos for the first time. The candelaria and pyrorhynchus groups are defined and commented on. Intraspecific variation in the colour of the hind wings is recorded for the first time in Pyrops condorinus (Lallemand, 1960). A checklist of the 12 Vietnamese species of Pyrops and an illustrated key which can also be used for Laos, Cambodia and Southern Continental China, are given. Pyrops buomvoi sp. nov. is the first new species of Pyrops discovered in Indochina for more than 50 years. Intraspecific colour variation in the species of Pyrops is briefly discussed.